Institutional Repositories and Open Access Initiatives in Bangladesh: A New Paradigm of Scholarly Communication - Islam, Md. Anwarul; Akter, Rowshon (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
Nowadays, open access (OA) in its diverse forms constitutes the most interesting and promising model for the research output of an academic or research institution. The purpose of the present study is to discuss the situation of OA in the developing world, with a focus on Bangladesh. The study also addresses why OA is important for developing countries and which initiatives have been taken in Bangladesh. Finally, we discuss some challenging issues of OA and suggestions on how to overcome these issues. It is rather obvious that developing countries have always faced a lack of research information and were unable to afford sufficient subscriptions to journals. The other side of the picture is the poor dissemination of the research outcome in the developing world. In Bangladesh, only three organizations have their institutional repository and have a reasonable number of local OA journals. We will identify some problems that impede the process of building open access IR, or more generally an OA environment in Bangladesh. We are convinced, however, that we will witness in the near future a sustainable growth of open access initiatives, with more open access literature and digital repositories.